2013
DOI: 10.3928/01477447-20130624-11
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Temporary Versus No Clamping in TKA

Abstract: Use of closed drainage systems after total knee arthroplasty (TKA) is a routine practice. Currently, a debate exists regarding whether temporary or no clamping is optimal. A systematic review of the English literature was conducted, and randomized controlled trials comparing all forms of temporary or no clamping drainage were included. Two authors independently extracted articles and predefined data. Data were pooled using a fixed-effects model to perform the meta-analysis. Nine randomized controlled trials to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 25 publications
(102 reference statements)
0
22
1
1
Order By: Relevance
“…Each domain was measured as low bias, unclear bias, or high bias. The methodologic quality of the RCTs was evaluated using the modified Jadad scale, [15] which is a numeric scale that evaluates the quality of the randomization, double blinding, and withdraws and dropouts. Studies scoring 4 or more out of a total possible of 8 were considered to be of high quality.…”
Section: Methodsmentioning
confidence: 99%
“…Each domain was measured as low bias, unclear bias, or high bias. The methodologic quality of the RCTs was evaluated using the modified Jadad scale, [15] which is a numeric scale that evaluates the quality of the randomization, double blinding, and withdraws and dropouts. Studies scoring 4 or more out of a total possible of 8 were considered to be of high quality.…”
Section: Methodsmentioning
confidence: 99%
“…We assessed the methodological quality of the trials independently. The quality of the studies was assessed using the modified Jadad scale (Table ) . Studies achieving four or more points (from a maximum of eight) were considered to be of high quality.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, a recent meta‐analysis has confirmed that autologous shed blood transfusion is an effective method to reduce allogeneic blood transfusion . Other techniques used to reduce the blood loss are clamping the drain, retrograde injection of TXA through the drain, and closure without a drain . The current study by Oremus and coworkers suggests that TXA could potentially eliminate the need for surgical drains and autologous shed blood transfusion.…”
mentioning
confidence: 99%